Antibiotic prescribing in neonatal sepsis: an Australian nationwide survey - Brendan McMullan; Celia Cooper; Naomi Spotswood; Rodney James; Cheryl Jones; Christopher Blyth; Thursky Karen (BMJ Paediatrics Open)
Objective To evaluate quality and variation in antibiotic prescribing for neonatal sepsis.Design We analysed prescribing in hospitalised neonates using the National Antimicrobial Prescribing Survey in Australian neonates from 1 January 2014 to 31 December 2018.Setting Data from antibiotic point prevalence surveys performed in hospitals, ranging from rural hospitals to tertiary paediatric and maternity hospitals within Australia.Patients Admitted neonates <28 days of age from participating hospitals.Main outcome measures Variation and appropriateness in prescribing for neonatal sepsis and variation in dosing for gentamicin and benzylpenicillin across hospitals.Results A total of 415 prescriptions among 214 neonates from 39 different hospitals were included. The majority of prescriptions (342, 82.4%) were for neonates <7 days of age. The most commonly prescribed antibiotics were gentamicin and benzylpenicillin, with 323 (77.8%) prescriptions. Dosing variability was substantial, with doses ranging from 2 to 8 mg/kg for gentamicin (median 5 mg/kg, IQR 4–5) and from 45 to 72 mg/kg for benzylpenicillin (median 60 mg/kg, IQR 50–60), although only 13 (3.2%) and 19 (4.6%) prescriptions were locally assessed as inappropriate or non-compliant with guidelines, respectively. At time of audit, 22% of antibiotics had been given for more than 48 hours and 9% more than 72 hours, although microbiologically confirmed infection was documented in only nine (4.2%) neonates.Conclusions Prescribing for neonatal sepsis was dominated by use of benzylpenicillin and gentamicin with substantial variation in dosing. A small minority had culture-confirmed infection. Efforts to standardise antibiotic dosing and duration for suspected neonatal sepsis are recommended.